2022
DOI: 10.1088/1361-6528/ac547a
|View full text |Cite
|
Sign up to set email alerts
|

Review on 3D growth engineering and integration of nanowires for advanced nanoelectronics and sensor applications

Abstract: Recent years have witnessed increasing efforts devoted to the growth, assembly and integration of quasi-one dimensional (1D) nanowires (NWs), as fundamental building blocks in advanced three-dimensional (3D) architecture, to explore a series of novel nanoelectronic and sensor applications constructed. An important motivation behind is to boost the integration density of the electronic devices by stacking more functional units in the out-of-plane z-direction, where the NWs are supposed to be patterned or grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…Si MWs can be fabricated using a variety of methods, including chemical etching, electrochemical etching, and vapor-liquid-solid growth. However, it is typically fabricated by using lithography and etching techniques (top-down), or bottom-up self-assembly approaches and they can have diameters ranging from a few nanometers to several micrometers [22]. Xiaomeng Zhang et al successfully fabricated microscale Si structures with ultra-high aspect ratio and smooth sidewalls on a four-inch wafer using metal-assisted chemical etching.…”
Section: Si Mw Fabrication Processmentioning
confidence: 99%
“…Si MWs can be fabricated using a variety of methods, including chemical etching, electrochemical etching, and vapor-liquid-solid growth. However, it is typically fabricated by using lithography and etching techniques (top-down), or bottom-up self-assembly approaches and they can have diameters ranging from a few nanometers to several micrometers [22]. Xiaomeng Zhang et al successfully fabricated microscale Si structures with ultra-high aspect ratio and smooth sidewalls on a four-inch wafer using metal-assisted chemical etching.…”
Section: Si Mw Fabrication Processmentioning
confidence: 99%
“…Semiconductor nanowire arrays are one-dimensional nanostructures that have drawn a great deal of attention over the past decade [1][2][3][4][5]. Through efficient carrier confinement in two dimensions and excitation of radial and longitudinal optical modes, many applications and functionalities have been enabled by semiconductor nanowire arrays [6].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, micro-Raman spectroscopy was widely used to study the stress in micrometer-sized structures [15][16][17][18][19]. With the semiconductor device approaching nanometer size, it is reported that there was no stress in vertically grown SiNWs [20,21]. While stress is essential in GAA NS transistor fabricated by CMOS process [22], the stress characterization by Raman spectroscopy is of great potential, but has not been fully investigated yet.…”
Section: Introductionmentioning
confidence: 99%